Bipolar patients referred to specialized services of care: Not resistant but impaired by sub-syndromal symptoms. Results from the FACE-BD cohort. (October 2015) - Henry, Chantal; Etain, Bruno; Godin, Ophelia; Dargel, Aroldo Ayub; Azorin, Jean-Michel; Gard, Sébastien; Bellivier, Frank; Bougerol, Thierry; Kahn, Jean-Pierre; Passerieux, Christine; Aubin, Valerie; Courtet, Philippe; et al.
Objective: A national network of expert centers for bipolar disorders was set up in France to provide support, mainly for psychiatrists, who need help for managing bipolar disorder patients. The aims of this article are to present the main characteristics of the patients referred to an expert center in order to highlight the major disturbances affecting these patients and to understand the most significant difficulties encountered by practitioners dealing with bipolar disorder patients. Methods: Patients were evaluated by trained psychiatrists and psychologists, with standardized and systematic assessment using interviews and self-report questionnaires. Results: All patients ( n = 839) met Diagnostic and Statistical Manual of Mental Disorders–Fourth Edition criteria for bipolar disorder I (48.4%), bipolar disorder II (38.1%) or bipolar disorder–not otherwise specified (13.5%). Mean illness duration was 17 years (±11.3), with 41.9% of patients having a history of suicide attempts. Lifetime comorbidities were 43.8% for anxiety disorders and 32.8% for substance abuse. At the point of inclusion, most patients (76.2%) were not in an acute phase, being considered to have a syndromal remission, but which still required referral to a tertiary system of care. Among these patients, 37.5% had mild to moderate residual depressive symptoms (Montgomery and Asberg Depression Rating Scale ranging from 7 to 19) despite 39% receiving an antidepressant. However, 47.8% were considered to be poorly adherent to medication; 55% showed evidence of sleep disturbances, with half being overweight; 68.1% of patients showed poor functioning (Functioning Assessment Short Test ⩾ 12) with this being linked to residual depressive symptoms, sleep disturbances and increased body mass index. Conclusions: It appears that bipolar disorder patients referred to an expert center in most cases do not suffer from a severe or resistant illness but they rather have residual symptoms, including subtle but chronic perturbations that have a major impact on levels of functioning. The longitudinal follow-up of these patients will enable a better understanding of the evolution of such residual symptoms.